Edumatriks Application-Based Quality Index Version 1.0 for Quality Control of Dance Studio Management and Education - Agus Budiman; Purnomo Purnomo; Saian Badaruddin; Muhammad Fairul Azreen Mohd Zahid (Yayasan Keluarga Guru Mandiri, 2026)
The quality of the implementation of dance studios as non-formal educational institutions can be measured through the quality of program execution and the management systems applied. Dance studios function not only as spaces for arts education but also as culture-based business units that require quality control to ensure the achievement of performance targets, service quality, and business objectives. However, preliminary studies indicate that most dance studios in Indonesia have not yet implemented standardized and modern management systems. This study aims to describe the development of a web-based application, Quality Index version 1.0, as an instrument for standardizing business processes and controlling the quality of dance studio management in Indonesia. The research employs a development research method with a descriptive qualitative approach, analyzing the design, functions, and initial implementation of the Quality Index application version 1.0. The results show that the application can present a database of dance studios based on established quality standards and facilitate the direct collection of management data through on-site assessments. The application serves as a systematic, measurable quality control tool. It is concluded that the Edumatriks Quality Index version 1.0 has the potential to serve as a standard quality parameter for dance studio management. This research contributes to the development of technology-based evaluation and management models in community dance arts education.